ANALISIS OVERREACTION DI BURSA EFEK INDONESIA PERIODE 2004-2008 - Muliasari Pinilih (Pro Bisnis, 2012)
The issue of this research are (1) whether there is overreaction in Indonesia Stock Exchange in the period 2004-2008 and (2) whether there is overreaction after controlling size and risk in Indonesian Stock Exchange in the period 2004-2008. The aim of this research are (1) to study and analyze whether there is overreaction in Indonesian Stock Exchange and (2) to study and analyze whether there is overreaction after controlling size and risk in Indonesian Stock Exchange. The hypothesis of this research are (1) occurs return reversal in winner portfolio, (2) occurs return reversal in loser portfolio, and (3) occurs overreaction after controlling size and risk. To answer hypothesis (1) and (2) use the market adjusted model and to answer hypothesis (3) is used regression Zero Cost Investment Portfolio with size and risk adjusted return method.The result of this research are (1) in the winner portfolio return reversal does not occur in the test period, (2) in the loser portfolio return reversal occurred in the test period and (3) there is no overreaction after controlling size and risk From the analysis, we can concluded (1) return reversal only occurs in loser portfolio and the return reversal does not occur in the winner portfolio, (2) after controlling for size and the risk was found that there is no overreaction in Indonesia Stock Exchange. The implication of this research is investors can use the contrarian strategy (buy low, sell high) to get abnormal return but investors should remain cautious in dealing with all sorts of changes that occurred in the capital market.Keyword : overreaction, winner-loser anomaly, size and risk